If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -9i)(x + -3i) = 0 Reorder the terms: (-9i + 3x)(x + -3i) = 0 Reorder the terms: (-9i + 3x)(-3i + x) = 0 Multiply (-9i + 3x) * (-3i + x) (-9i * (-3i + x) + 3x * (-3i + x)) = 0 ((-3i * -9i + x * -9i) + 3x * (-3i + x)) = 0 Reorder the terms: ((-9ix + 27i2) + 3x * (-3i + x)) = 0 ((-9ix + 27i2) + 3x * (-3i + x)) = 0 (-9ix + 27i2 + (-3i * 3x + x * 3x)) = 0 (-9ix + 27i2 + (-9ix + 3x2)) = 0 Reorder the terms: (-9ix + -9ix + 27i2 + 3x2) = 0 Combine like terms: -9ix + -9ix = -18ix (-18ix + 27i2 + 3x2) = 0 Solving -18ix + 27i2 + 3x2 = 0 Solving for variable 'i'. Factor out the Greatest Common Factor (GCF), '3'. 3(-6ix + 9i2 + x2) = 0 Factor a trinomial. 3((3i + -1x)(3i + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(3i + -1x)' equal to zero and attempt to solve: Simplifying 3i + -1x = 0 Solving 3i + -1x = 0 Move all terms containing i to the left, all other terms to the right. Add 'x' to each side of the equation. 3i + -1x + x = 0 + x Combine like terms: -1x + x = 0 3i + 0 = 0 + x 3i = 0 + x Remove the zero: 3i = x Divide each side by '3'. i = 0.3333333333x Simplifying i = 0.3333333333xSubproblem 2
Set the factor '(3i + -1x)' equal to zero and attempt to solve: Simplifying 3i + -1x = 0 Solving 3i + -1x = 0 Move all terms containing i to the left, all other terms to the right. Add 'x' to each side of the equation. 3i + -1x + x = 0 + x Combine like terms: -1x + x = 0 3i + 0 = 0 + x 3i = 0 + x Remove the zero: 3i = x Divide each side by '3'. i = 0.3333333333x Simplifying i = 0.3333333333xSolution
i = {0.3333333333x, 0.3333333333x}
| 7(4y+5)=19y+8 | | 2y+y+9y= | | 15y=6y^2 | | a+1+a+3+2a=180 | | 1+3s=4 | | a+1+a+3+2a=90 | | x*y=31 | | 16f=1.8+32 | | c=2a+3 | | m/36=2 | | dxy=31 | | F(x)=-2x^2-5x+7 | | 7(x+5)+5=9x-2(x-4) | | 70=6p+34 | | 16=2a+5 | | 3x+5+6x-9=-4 | | -45=32 | | 4=-7s+53 | | 6b-3b=0 | | 50+d=2d | | 5x+x+20+40=180 | | x+y-12x+8y-8=0 | | 5x-64/9=64 | | 7(4y+5)=19+8 | | -u+2=220 | | w=x(y/z) | | N/0.6=8 | | 6=3a+3 | | 30-x=5x+6 | | -43+x=23-2x | | 33.6=H^(3/2) | | 2w+10=48 |